Measuring the Market Power of China's Medical Product Exports - Wu, Wanshan; Zhang, Hao; Huang, Leping; Wang, Lijun (Frontiers in Public Health, 2022)
During the COVID-19 pandemic, medical products have been crucial to the global fight against the disease. As a major manufacturing country, China occupies an important position in the medical products field. However, China's terms of trade are not commensurate with its status as a major exporter of medical products. Therefore, studying China's market power in medical product exports has important practical significance for determining China's value chain position in the global market and then proposing policies and measures to enhance China's market power. The findings of this paper, utilizing HS six-digit data from 1992 to 2020, illustrate that China's market power is only in limited medical product export markets. Accordingly, we propose countermeasures to enhance the market power of China's medical product exports.